2017
DOI: 10.1515/cpp-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

The correlations between air pollution and depression.

Abstract: Introduction: In the 21st century there is an increased prevalence of depression in the world. So far the mechanism of developing depression has not been exactly known. Risk factors of depression occurrence are complex and nowadays it has been emphasized that air pollution can affect the intensity of depressive symptoms.Objective: The analysis of the scientific works investigating the correlations between air pollution and depression.Material and method: The material consisted of the studies published between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Clinical evidence from China, the United States and the European Union concluded that a 10 µg/m 3 increase in PM 10 led to a significant rise in COPD exacerbation and deaths. In another study, [ 11 ] epidemiological and pathobiological evidence confirmed that both short and long-term exposure to air pollution increased stroke risk, and in other studies, it was found that air pollution could also be associated with other diseases and symptoms, such as still births [ 12 ], depression [ 13 ] and Alzheimer’s [ 14 ].…”
Section: Literature Reviewmentioning
confidence: 82%
“…Clinical evidence from China, the United States and the European Union concluded that a 10 µg/m 3 increase in PM 10 led to a significant rise in COPD exacerbation and deaths. In another study, [ 11 ] epidemiological and pathobiological evidence confirmed that both short and long-term exposure to air pollution increased stroke risk, and in other studies, it was found that air pollution could also be associated with other diseases and symptoms, such as still births [ 12 ], depression [ 13 ] and Alzheimer’s [ 14 ].…”
Section: Literature Reviewmentioning
confidence: 82%
“…Shahrom [ 93 ] described stress as a feeling of discomfort in oneself that influences the mind, however, according to Fadzillah-Kamsah, stress covers the following feelings: burden, worry, strain, conflict, pressure, feeling, fatigue, helplessness, panic, and depression [ 94 ]. Sahari et al [ 94 ] comprehensively reviewed stress, and Łopuszańska and Makara-Studzińska [ 21 ] provided an overview of air pollution-associated depression.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures and air pollution are also associated with low mood and potency [ 16 , 17 ], changes in sexual behavior, and negative effects on reproductive health [ 17 , 18 ]. The World Bank [ 19 ] has provided an excellent updated insight of the fertility rate for all countries around the world, based on total births per woman, which could be linked to global warming/greenhouse gases and air pollution [ 17 , 20 , 21 ]. Kihal-Talantikite et al [ 22 ] extensively reviewed the adverse impacts of proximity to polluted areas on the outcomes of pregnancy, such as infant mortality, premature birth, low birth weight, congenital malformation, intrauterine growth retardation, and gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…With the novelty of the mental health research, limited literature reviews have been completed in this field. Of those available, Łopusza ńska and Makara-Studzi ńska [29], Gładka et al [30], Zeng et al [31], and Borroni et al [32] focus only on depression and, in the case of Gładka et al [30], suicide. Buoli et al [33] provides an encompassing view of many different mental health disorders.…”
Section: Methodology Considerations and Contribution Of Researchmentioning
confidence: 99%